Reflections of students and staff in a project-led partnership: Contextualised experiences of students-as-partners - Dianati, Seb; Oberhollenzer, Yvonne (International Journal for Students as Partners, 2020)
For many years, the methods of teaching and learning have remained relatively unchanged, with teachers bestowing knowledge to their students in a one-way hierarchical approach to learning. However, Student as Partners (SaP) as a concept and an ideology aims to disrupt traditional power structures of learning to offer a shared space where students become co-creators of change. This research reflects on one particular SaP project, a small-scale, project-based, institutionally resourced partnership whereby 14 students collaborated alongside 3 staff members to enhance the quality of the student experience at an Australian university. The current study aims to explore what factors mediate newly formed student-staff partnerships. Using a qualitative thematic approach, the paper draws from various online surveys to share particular contextualised experiences of student-staff partnerships. These include: learning together and navigating power dynamics, opportunities to build relationships, and balancing work and study. They became the specific strategies that mediated effective partnership. The implications of these themes highlighted that the context-dependent nature of SaP should be realised in an effort to develop institutionally appropriate practices.